The Relationship Between Self-Efficacy, Aerobic Fitness, and Traditional Risk Factors for Musculoskeletal Injuries in Military Training: A Prospective Cohort Study - Brian R Kreisel; Kelly M Scott; Erin M Florkiewicz; Michael S Crowell; Jamie B Morris; Paige A McHenry; Timothy M Benedict (International Journal of Sports Physical Therapy)
# Background